Annular pancreas presenting as gastric outlet obstruction in adult: A rare case report - Kumar Mishra, Rohit; Raya, Akash; Shah, Jay Narayan; Shrestha, Alok; Kumar Yadav, Basanta (Journal of Chitwan Medical College, 2026)
Annular pancreas (AP) is a rare congenital anomaly where pancreatic tissue encircles the duodenum. While typically presenting in infancy, adult-onset AP is uncommon and often masquerades as other upper gastrointestinal pathologies, making it a diagnostic challenge. This report highlights an adult case of AP presenting with classic gastric outlet obstruction.